Beyond the Mask: Analysis of Error Patterns on the KTEA-3 for Students With Giftedness and Learning Disabilities. (February 2017) - Ottone-Cross, Karen L.; Dulong-Langley, Susan; Root, Melissa M.; Gelbar, Nicholas; Bray, Melissa A.; Luria, Sarah R.; Choi, Dowon; Kaufman, James C.; Courville, Troy; Pan, Xingyu
An understanding of the strengths, weaknesses, and achievement profiles of students with giftedness and learning disabilities (G&LD) is needed to address their asynchronous development. This study examines the subtests and error factors in the Kaufman Test of Educational Achievement–Third Edition (KTEA-3) for strength and weakness patterns of students with G&LD in higher and lower level thinking skills by comparing G&LD students ( n = 196) with academically gifted (GT; n = 69) and specific learning disability (SLD) students ( n = 90). Several one-way MANCOVAs were conducted with subtest error factor scores as dependent variables and grouping variable (G&LD, GT, or SLD) as the independent variable. The G&LD means scores across subtests were in between the two control groups. On many higher level thinking tasks, the G&LD group scored similar to the gifted group. The results support the use of error analysis to gain further understanding into the profile of students with G&LD.